Self-employment in China: Are rural migrant workers and urban residents alike? - Yuling Cui; Daehoon Nahm; Massimiliano Tani (Institute for the Study of Labor (IZA), 2013)
This paper studies differences in the motivation to be self-employed between rural migrants and urban residents in modern China. Estimates of the wage differential between self-employment and paid-employment obtained through a three-stage methodology using the 2002 China Household Income Project (CHIP), reveal that rural migrants become self-employed to avoid low-pay city jobs, enhancing their odds of economic assimilation. Conversely, urban residents become entrepreneurs to move out of unemployment. The empirical analysis confirms that self-employment also attracts married individuals and those in good health, while it negatively relates to high educational attainment. The decomposition of hourly wage differences between pairs (by type of employment and residence status) shows that higher hourly wages of paid and self-employed urbanites over migrants predominantly arise through differences in coefficients (i.e. discrimination) while those between self- and paid employment among urbanites are mostly due to differences in individual characteristics. Discrimination overwhelmingly accounts for hourly wage differences between self- and paid employment among rural immigrants. We interpret the relevant effect of discrimination in 2002 in urban labour markets as a sign of the institutional barriers associated with the Hukou system.
Keywords: C36; J61; J31; J21; J24; 330; self-employment; wage differentials; rural migrant workers; urban residents